Agglutination of Intravenously Administered Phosphatidylcholine‐Containing Lipid Emulsions With Serum C‐reactive Protein. (1st March 2013) - Tugirimana, Pierrot; Speeckaert, Marijn M.; Fiers, Tom; De Buyzere, Marc L.; Kint, Jos; Benoit, Dominique; Delanghe, Joris R.
Abstract : Background : C‐reactive protein (CRP) is able to bind phospholipids in the presence of calcium. We wanted to investigate the reaction of CRP with various commercial fat emulsions and to explore the impact of CRP agglutination on serum CRP levels. Materials and Methods : Serum specimens were mixed with Intralipid 20% (soybean oil–based fat emulsion), Structolipid (structured oil–based fat emulsion), Omegaven (fish oil–based fat emulsion), or SMOFlipid (mixed soybean oil–, olive oil–, and fish oil–based emulsion) in Tris‐calcium buffer (pH 7.5). After 30 minutes of incubation at 37°C, CRP‐phospholipid complexes were turbidimetrically quantified and flow cytometric analysis was performed. Similarly, CRP complexes were monitored in vivo, following administration of fat emulsion. Results : CRP was able to agglutinate phospholipid‐containing lipid droplets present in the soybean oil–based fat emulsion and the structured oil–based fat emulsion. To a lesser extent, agglutination was observed for fish oil–containing fat emulsions, whereas no agglutination was noticed for the mixed soybean oil–, olive oil–, and fish oil–based emulsion. Results for propofol‐containing emulsions were comparable. Agglutination correlated with phospholipid content of the emulsions. When in vivo agglutination occurred, plasma CRP values dropped due to consumption of CRP by phospholipid‐induced agglutination. Conclusions : In this in vitro experiment, we demonstrated agglutination of CRP with phospholipids in various fat emulsions. Research studies are required in patients to determine which effects occur with various intravenous fat emulsions.